Germination Response of some Forest Tree Seeds under Controlled Conditions - Gupta, B. N.; Pattanath, P. G. (Indian Forester, 1976)
This paper deals with the fundamental and practical aspects of germination behaviour of seeds of a number of tree species. Variations in germination percentage under different conditions of temperature and media have been studied and the significance of these variations have been discussed. Based on these data, geermination test rules have also been framed for eleven species of forest tree seed which were not included in earlier publications.